Answer
Substitute w by 7
7^3
7x7x7 =343
Answer
X-2y = 2
3x + y = 6
Ox=-2
Ox=0
Ox=2
Ox=3
= 0
Step-by-step explanation:
easy
Answer:
3n - 5
Step-by-step explanation:
f(n) = 3n - 5. Works for all of them
Answer:
22
Step-by-step explanation:
(4 x 4) + (2 x 3) = 16 + 6 = 22
We know the distance formula is
![\sqrt{ (x_{2}-x_{1})^2+ (y_{2}-y_{1})^2 }](https://tex.z-dn.net/?f=%20%5Csqrt%7B%20%28x_%7B2%7D-x_%7B1%7D%29%5E2%2B%20%28y_%7B2%7D-y_%7B1%7D%29%5E2%20%7D%20%20%20)
9)
Here A( -4,2) and B(1,4)
So length of AB
= ![\sqrt{(1-(-4))^2+(4-2)^2} =\sqrt{5^2+2^2} =\sqrt{29}](https://tex.z-dn.net/?f=%20%5Csqrt%7B%281-%28-4%29%29%5E2%2B%284-2%29%5E2%7D%20%3D%5Csqrt%7B5%5E2%2B2%5E2%7D%20%3D%5Csqrt%7B29%7D%20%20%20)
Also C(2,1)
Length of BC
= ![\sqrt{(2-1)^2+(-1-4)^2} =\sqrt{1^2+(-5)^2} =\sqrt{26}](https://tex.z-dn.net/?f=%20%5Csqrt%7B%282-1%29%5E2%2B%28-1-4%29%5E2%7D%20%3D%5Csqrt%7B1%5E2%2B%28-5%29%5E2%7D%20%3D%5Csqrt%7B26%7D%20%20%20%20%20)
So we can see that length of AB is not equal to length of BC
11.
Now AB = ![\sqrt{29}](https://tex.z-dn.net/?f=%20%5Csqrt%7B29%7D%20%20)
Also C(2,-1) & D(4,4)
Length of CD
= ![\sqrt{(4-2)^2+(4-(-1)) ^2} =\sqrt{2^2+5^2} =\sqrt{29}](https://tex.z-dn.net/?f=%20%5Csqrt%7B%284-2%29%5E2%2B%284-%28-1%29%29%20%5E2%7D%20%3D%5Csqrt%7B2%5E2%2B5%5E2%7D%20%3D%5Csqrt%7B29%7D%20%20%20)
Yes AB = CD